THE EFFECTS OF READING HABIT AND VOCABULARY MASTERY TOWARDS STUDENT’S SPEAKING SKILL - Doni Anggoro Ari Santoso (Deiksis, 2014)
The purpose of this study is as follows: to obtain empirical data and analyze The Effects of Reading Habit and Vocabulary Mastery towards Student's Speaking Skill in vocational schools in East Jakarta. Calculations were performed in this study was descriptive statistics, testing normality using the Kolmogorov-Smirnov test, ANOVA tables. The research was conducted in vocational schools in East Jakarta. Data retrieved by providing test Reading Habit / reading habits (questionnaire of 20 numbers), Vocabulary Matery / vocabulary (multiple-choice and match as many as 20 questions), and test speaking skills / ability to speak (interview by 3 numbers) given to students in grade ten on 10 November and SMK SMK PGRI 20 Jakarta Timur.Berdasarkan results obtained, it can be concluded that there are significant between the reading habits of the students' speaking ability (Sig = 0.006 and ttest = 2.940; while TTable = 1.68). There is the influence of vocabulary on their speaking ability (Sig = 0.000 and ttest = 5,336; while TTable = 1.68). There is the influence of the habit of reading and vocabulary of the students' speaking ability (correlation coefficient = 0.850 and the coefficient of determination = 72.2%).Keywords: the habit of reading, vocabulary, and speaking skills